PENGARUH KONFORMITAS TERHADAP PERILAKU DISIPLIN BERLALU LINTAS PADA MASAHISWA DENGAN SEPEDA MOTOR DI JAKARTA - Abdullah Farkhan; Burhanuddin Tola (Journal of Research and Measurement in Psychology, 2013)
Abstract Purpose of this research is to detect how much the conformity influence the behavior of traffic discipline in students with a motorcycle in Jakarta. This research using quantitative method with ex post facto research design and using accidental sampling technique. Population in this research were all Universitas Negeri Jakarta students which ride a motorcycle as main transportation. The sample of this research are 40 respondents. This research used regression analysis with SPSS version 17.00 as analysis data technique. Based on the results of the data, the F value is 9,757 with 0,003 as significance level. Regression equation, Y = 69,782 + (-) 0,382X and the influenced of (R square) variable are 20,4 %, 79,6 % remaining are infuenced by the other factors than conformity. Based on this calculation Ho is rejected and Ha is accepted, so that can be concluded that there is a significant negative effect between conformity and traffic discipline in Universitas Negeri Jakarta students were ride a motorcycle, and it means if the conformity of Universitas Negeri Jakarta students which ride a motorcycle was increase so, the disciplinary of them was decrease. Keywords: conformity, discipline, traffic